Bio-indicators of nitrogen pollution in heather moorland - Edmondson, J.L.; Carroll, J.A.; Price, E.A.C.; Caporn, S.J.M. (The Science of the total environment, 2010)
Heather moorlands are internationally important ecosystems that are highly sensitive to eutrophication and acidification by reactive atmospheric nitrogen (N) deposition. We used a long-term experiment simulating wet-deposition of N on heather moorland to identify potential bio-indicators of N deposition. These indicators were subsequently employed in a survey covering a N deposition gradient ranging from approximately 7 to 31 kg N ha − 1 yr − 1 , at selected sites throughout the UK. In this regional survey litter phenol oxidase activity and bryophyte species richness were negatively associated with N deposition. Calluna vulgaris N:P ratios and litter extractable N were positively correlated with N deposition. The use of the suite of four bio-indicators has the potential to provide rapid assessment of the extent of N saturation of heather moorland sites and moorland ecosystem functioning, and has significant advantages over reliance on single measures such as soil N status or an individual bio-indicator species.